Quantum antennas - Parthasarathy, Harish (Abingdon, Oxon : CRC Press, 2021)
This book is about several questions regarding how to describe the quantization of the current density in an antenna and about the nature of the quantum electromagnetic field produced by such a quantum current density. The second quantized current density can be built out of the Dirac field of electrons and positrons while the free electromagnetic or photon field is built out of solutions to the wave equation with coefficients being operators, namely the creation and annihilation operators of the photons. Note: T&F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
OCLC-licensed vendor bibliographic record.
Keywords: Electrodynamics; SCIENCE / Physics; SCIENCE / Quantum Theory; SCIENCE / Electromagnetism